Evaluation of the Socio-Economic Survey and Statistical Metrics for Lambhvel Village, Gujarat State - Umang Raichura; Devang Rathod; Dhrumil Gajera; Mayur Sevak (International Journal of Engineering and Management Research, 2023)
This study is aimed to research the life of people of village Lambhvel, Gujarat, awareness about various government schemes, about their family, and what they are expecting from the government for the betterment of their life. This survey is part of NSS Village Camp 2023 which was held from 22nd May to 27th May at Lambhvel, Anand, Gujarat. This survey is done on 23rd May. Which total of the 40-person personal interview has taken at Lambhvel. Of 40 persons 30% are women and 70% are men. Of which 40% are self-employed and 15% are farmers only. 87.5% are having ration cards and out of it, 70% of people are taking ration from it which means the BPL rate is very high in the village. 92.5% are having Aadhar card. An average of 5.075 persons are living in one house and each house has an average of 0.75 Girls and 1.075 boys in each house. And 1.825 Children in each house, which means there are 2 adults and 2 children in one house but we can also see that some house has 5 or 8 children in one house. The average income of one house by our survey is Rs 85300. This village has very less awareness about any government scheme because 17.5% of people are taking benefit of any Government scheme and most of the people out of 17.5% are taking benefit of Pradhan Mantri Ujjwala Yojana (PMUY) and 35% of people having Maa Card/ Aayushman Card. And most people want cleanliness in the city and a better education system in their village for their children.